2006
DOI: 10.1002/dc.20439
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration diagnosis of Hodgkin lymphoma using current WHO classification—Re-evaluation of cases from 1999–2004 with new proposals

Abstract: With the advent of modern therapy, the differences in prognoses and treatment regimens among different subtypes of Hodgkin lymphoma (HL) have largely vanished. Stage and the presence of systemic symptoms are much more important than histologic subtypes as predictive factors. The current (2001) WHO classification markedly de-emphasizes spatial relationships as critical to the diagnosis of lymphoma and emphasizes cell morphology, immunophenotype, genetic features, and clinical information to define the disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…However, if the diagnosis of Hodgkin lymphoma had already been established, the findings of these cells were sufficient to make a diagnosis. However, Zhang et al [36] concluded that classic binucleated or multinucleated R-S cells were infrequent in many cases and the clue to the diagnosis of Hodgkin lymphoma in such situation was the frequently encountered atypical mononuclear R-S cell variant with prominent macronucleoli and granuloma together.…”
Section: Discussionmentioning
confidence: 97%
“…However, if the diagnosis of Hodgkin lymphoma had already been established, the findings of these cells were sufficient to make a diagnosis. However, Zhang et al [36] concluded that classic binucleated or multinucleated R-S cells were infrequent in many cases and the clue to the diagnosis of Hodgkin lymphoma in such situation was the frequently encountered atypical mononuclear R-S cell variant with prominent macronucleoli and granuloma together.…”
Section: Discussionmentioning
confidence: 97%
“…As a diagnostic procedure, FNA is very attractive because no sedation is required. A recent study reported several new immune stains to enhance diagnostic accuracy that may limit the need for a tissue biopsy [14]. Modern immunostaining techniques were used on the FNA sample; and the diagnosis, subclassification, and grading studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are based on small retrospective series of cases and may suffer from selection bias. FNA diagnosis of HL lesions may be associated with a false negative rate of 15–40% [52, 66, 69]. Generally, because of diagnostic errors that may occur even with the best histologic preparations, FNA samples are not considered reliable enough for the diagnosis and classification of HL.…”
Section: Diagnosismentioning
confidence: 99%